Evaluación del efecto del agua magnetizada en la primera fase del desarrollo fenológico de Amaranto (Amaranthus caudatus) variedad Selenaya Sosulka, Latacunga-Cotopaxi, 2021. - Tapia Chiguano, Byron Germanico (2021)
This research was carried out at the Salache Academic Experimental Center of the Technical University of Cotopaxi; the research is part of the Intelligent Greenhouse and Andean Grains projects; at an altitude of 2733 m. The general objective was: To evaluate the effect of magnetized water in the first phase of phenological development of Amaranth (Amaranthus caudatus) Selenaya Sosulka variety, as specific objectives: To analyze the behavior of the physical-chemical properties of soil and water when subjected to magnetic fields. To characterize the agronomic behavior of Amaranth (Amaranthus caudatus) Selenaya Sosulka variety with the application of magnetized water. A Randomized Complete Block Design was applied with 4 treatments and 4 replications, obtaining 16 experimental units. Magnetized water was applied at 3 intensities, T1: 1000 gauss neodymium magnet; T2: 2 magnets one neodymium and one mineral magnet 3000 gauss, T3: 1 neodymium magnet plus two mineral magnets 5000 gauss and a control. The result of the water after being treated with magnetization shows that there is variation, changes in the chemical properties compared to the control. Treatment 1 shows 196 mg/l hardness of CaCO3, being moderately hard, pH of 7.97 basic, electrical conductivity of 412 moderate range, alkalinity of 3.822, TDS mg/l of 207, SO4 of 24, NO3 1.4 and chlorine level of 0.10. Treatment 2 hardness 166 mg/l CaCO3 being moderately hard, pH of 7.92 basic, electrical conductivity of 417 moderate range, alkalinity of 3.822, TDS mg/l of 209, SO4 of 22, NO3 1.7 and chlorine level 0.10. Treatment 3 hardness 146mg/l CaCO3 being moderately hard, pH of 7.9 basic, electrical conductivity of 420 moderate range, alkalinity of 2.254, TDS mg/l of 210, SO4 of 22, NO3 1.7 and chlorine level 0.10. Treatment 4 unmagnified water shows hardness of 256 mg/l CaCO3 being hard water, pH of 8.02 basic, electrical conductivity of 419 moderate range, alkalinity of 2.842, TDS mg/l of 210, SO4 of 21, NO3 1.3 and chlorine level 0.20. The soil results show changes when irrigation with magnetization is applied, the parameters analyzed are pH and electrical conductivity change. Having an initial soil pH of 7.96 and electrical conductivity of 0.33. Treatment 4 without magnetization has a pH of 8.53 and electrical conductivity decreases to 0.28. Treatment 1 a pH of 8.36 and 0.27 electrical conductivity decreases with increasing magnetic intensity. Treatment 2 a pH of 8.26 and electrical conductivity increases to 0.32. Treatment 3 a pH of 8.25, in electrical conductivity decreases to 0.29. The effect of the magnetic field on Amaranth plants has been investigated through drip irrigation, the results reveal beneficial effects on agronomic variables and continue to evaluate the application of magnetized water in different crops and phenological stages apply the magnetization of water, performing previous analysis to evaluate the elements that varied, such as pH and boron.